Microstructural evaluation of sn3.0ag0.5cu solder alloy fabricated via powder metallurgy method - Nadhrah, Murad (2021)
For decades, casting has been the most influential industrial manufacturing process to fabricate and promote higher properties of solder alloy. However, stirring technique which is commonly applies in casting method has brought some attentions for further discussions. According to literatures, the stir casting technique has showed quality issue towards solder alloy property of elementary particles distribution. Thus, concerning the issue, a green technology known as Powder Metallurgy(PM) method is selected due to its material processing function which can also offer particle distribution deals. It is basically having two basic procedures which are milling and compacting. These works for better solder alloy production where it only uses room temperature to consolidate different materials at once. Moreover, a clean and safer working environment is in practice and it takes one mould to produce dozens of products which is a big cost saving. This study is conducted to seek out the gap found in the literature reviews on the homogeneity issue of the solder alloy’s elemental distributions. Thus, this research is carried out to study the properties of Sn3.0Ag0.5Cu solder alloy prepared by PM method. The selection of materials involving size and shape of the raw materials are important factors whilst practising PM method due to the end up result of milling. Therefore, four different milling durations listing 2, 4, 6 and 8 hours which became the variables to reach off a homogenize granulated mixture inside the alloy. These mixtures were then compacted with a hydraulic press machine for 1, 3, 5, 7 and 9 ton of compaction loads. This step is to ensure the mixture will be in handable form to move on into reflow test procedure as well as the microhardness test. Through the reflow test, there are four major topics to be discussed on including the behaviour of solder pallet by reflow test, wettability test, formation of IMC and the thickness of IMC. All samples are cooled down by the slow cooling process. Results showed that there is high possibility to utilize PM method in solder alloy fabrication due to high distribution of different elements after milling process as being confirmed by the SEM and EDX analyses, high degree of wettability by all samples which lined below 90°. The SEM and EDX also displayed scallop IMC of Cu6Sn5 existed at the solder joint and matrix. The IMC thickness depicted quite high values due to longer cooling time. In conclusion, PM method is a better option of solder alloy fabrication to practice Green Technology plus fits the low-cost production and safer environment. The produced solder alloy by this method also fits the excellent solder alloy properties.